UPPER TRIASSIC LOWER JURASSIC STRATIGRAPHY AND PALEOGEOGRAPHIC EVOLUTION OF THE ZANSKAR TETHYS HIMALAYA (ZANGLA UNIT) - FLAVIO JADOUL; EDUARDO GARZANTI; ELISABETTA FOIS (Rivista Italiana di Paleontologia e Stratigrafia, 2018)
The Upper Triassic-Lower Jurassic sedimentary succession of the Zanskar Tethys Himalaya (Ladakh, India) can be subdivided into three stratigraphic units: the Zozar Formation (Late Garnian), the Quartzite Series (Norian) and the Kioto Group (Rhaetian to Early Dogger).